Nutrient Dynamics in an Integrated Prawn (Penaeus latisulcatus Kishouye 1896) and Macroalgae (Sargassum sp.) culture system - Mai, Huong (Curtin University, 2009)
Rapid global expansion of the aquaculture industry has prompted the need for development of techniques for effective environmental management. In intensive aquaculture, effluents have resulted in environmental degradation of surrounding ecosystems. As a result, wastewater treatment techniques using biological means is growing worldwide. The present research was conducted to investigate the nutrient flows in a system where seaweed Sargassum sp. was integrated into western king prawn (Penaeus latisulcatus) culture.Three laboratory experiments were conducted to determine the nutrient load discharged from western king prawn culture and, the capacity of Sargassum sp. to reduce nutrient loads in the integrated culture system. The effects of changes in stocking biomass of prawns and seaweed on the growth rates of both species and nutrient flows in an integrated culture system were also investigated. Prawn and seaweed growth, prawn survival, water quality parameters, nitrogen and phosphorus contents in tissue of prawns, seaweed and feed were analysed.These experiments demonstrated that by integrating seaweed into prawn culture, the concentrations of total ammonium nitrogen (TAN), nitrite-nitrogen (NO[subscript]2[superscript]-) and nitrate-nitrogen (NO[subscript]3[superscript]-), dissolved inorganic nitrogen (DIN), total nitrogen (TN), phosphate (PO[subscript]4[superscript]3[superscript]-) and total phosphorus (TP) were significantly reduced (p ≤ 0.05) than in the prawn monoculture and remained within non-toxic limits for the duration of the experiment. Overall, Sargassum sp. removed a greater percentage of DIN (35.8-52.6%) and phosphate (5.62-65.9%) than other nutrient forms.The mean nutrient uptake rates of Sargassum sp. were 0.33-0.69 mg g[superscript]-[superscript]1 dry wt day[superscript]-[superscript]1 for nitrogen and 0.13-0.25 mg g[superscript]-[superscript]1 dry wt day[superscript]-[superscript]1 for phosphorus. The integrated culture systems effectively retained nutrients into harvested products in comparison to monoculture system. The rates of nutrient conversion into waste were significantly lower in the integrated culture systems (52.46-70.05% for nitrogen and 49.09-69.41% for phosphorus) than in prawn monoculture (82.31% for nitrogen and 85.53% for phosphorus).Integrating Sargassum sp. with prawn culture did not alter the specific growth rate (SGR) and survival rate of the prawns. The SGR of Sargassum sp. in integrated culture increased at the rate of 3.16 ± 0.74% day[superscript]-[superscript]1, while was 5.70 ± 0.82 % day[superscript]-[superscript]1 in seaweed monoculture. Decreasing the stocking biomass of Sargassum sp. negatively affected its growth rate and capacity in uptaking the nutrients.The results of this study suggest that integrating Sargassum sp. into prawn culture can benefit prawn farming by assisting in the maintenance of optimum water quality and thereby, reduce environmental impacts on surrounding ecosystems. However, the lower growth rate of seaweed cultured with prawns than those cultured in isolation suggests the presence of several limiting factors for the growth of the seaweed in integrated seaweed and prawn culture.